Monte Carlo Simulation of Spacecraft Reentry Aerothermodynamics and Analysis for Ablating Disintegration (Communications in Computational Physics, 2020)
It is important to have detailed knowledge of large scale spacecraft reenteringatmospheric disintegration and main structures melting ablation for an accurateestimate of debris spread area. The direct simulation Monte Carlo (DSMC) methodis performed to simulate aerothermodynamic characteristics of Tiangong-1 simplifiedconfiguration in rarefied transitional regime during its reentry process. The hybridCartesian and surface unstructured triangular meshes as well as adaptive refinementare employed to deal with these complex configuration flows. Internal energy excitationsand chemical reactions are considered to compute aero heating precisely. A large number of computational difficulties are solved by the DSMC parallel algorithmbased on MPI environment. Hypersonic nitrogen flow of Mach 15.6 about a 25/55deg biconic model is chosen as test cases for validation. The calculated pressure andheating rate distributions have good agreement with the experimental data. Based onthe DSMC results of Tiangong-1 shape, the structure stress of solar panels connectingmodel is analyzed with finite element method. The heat conduction and ablationcomputations are performed on thin shell structure of spacecraft with one-dimensionalmodel. The height of solar panels broken away from the spacecraft main body is preliminaryestimated. The melting ablation of two module structure vehicle is analyzedfor different reentering altitudes.
Keywords: Large scale spacecraft; solar panel; atmospheric reentry; aerothermodynamics; DSMC method; disintegration; melting ablation.